MAKING UV-BOX STERILIZER FOR PREVENTING COVID-19 WHEN REPAIRING DENTURES IN KEDIRI: PEMBUATAN STERILISATOR UV-BOX UNTUK PENCEGAHAN COVID-19 SAAT REPARASI GIGI TIRUAN DI KEDIRI - Kusdarjanti, Endang; Setyowati, Okti; Nur Halimah, Anisa; Goenharto, Sianiwati; Inayati, Eny; Redjeki I, Sri; Sujati; Laksmi LR, Mia (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: Dental technicians are individuals with unique qualities who collaborate with dentists. The quality of information and abilities must be improved on a regular basis. However, because there is no additional education accessible for dental technicians, many find it difficult to refresh their knowledge and abilities on modern dental technology. Dental technicians who are members of the Indonesian Association of Dental Technicians (PTGI) in Kediri City have not yet fully understood the consequences of Covid 19 infection when working on the process of making and repairing dentures, therefore, it is very necessary to be given training on how to make a simple UV sterilizer. box that can kill the Covid-19 virus. Objective: This training aims to provide dental technicians who are members of partners with information on how to prevent Covid-19 and construct a basic sterilizer. Method: Counseling and workshops for dental technicians affiliated with the Indonesian Dental Technicians Association (PTGI) in Kediri City, including information on how to prevent Covid-19 and how to make a simple UV-Box sterilizer. Results: Based on the training participants' pre-test and post-test results, it is clear that the average (mean) post-test score (86,957) is greater than the average pre-test score (58,152). Conclusion: The findings of the pre-test and post-test calculations indicate that the training participants' knowledge enhanced after attending counseling and training.